Exploring the therapeutic effects of Ulvan species (Ulva fasciata and Ulva rigida) on hyperglycemia, hyperlipidemia and adipose oxidative injury - S'thandiwe N. Magwaza; Veronica F. Salau; Kolawole A. Olofinsan; Md. Shahidul Islam (Scientific African)
This study elucidated the protective effects of two Ulvan seaweed species, Ulva rigida and Ulva fasciata on oxidative stress, obesity and diabetes related parameters, using in vitro, and ex vivo experimental models. Dried whole U. rigida and U. fasciata were used to obtain the crude aqueous and ethanol extracts. The in vitro studies were used to evaluate the effects of the seaweed extracts on key lipid and carbohydrate digestive enzymes including α- glucosidase, α- amylase and pancreatic lipase. For ex vivo studies, the intestinal glucose absorption inhibitory activities as well as muscle glucose uptake stimulating activities of the extracts were assessed. Furthermore, for antioxidant activities, the oxidative damage was induced by incubating the adipose tissue with 0.1 M ferrous sulphate (FeSO4), and then treated with the crude aqueous and ethanol extracts of Ulva rigida and Ulva fasciata for 30 min at 37°C. All the experiments were conducted using established methods. The aqueous extract of Ulva rigida exhibited strongest α- amylase and α- glucosidase inhibitory activities (IC50 96.29 µg/ml and 93.56 µg/ml), while the highest pancreatic lipase inhibition was depicted by the aqueous extract of Ulva fasciata (IC50 184.35 µg/ml). The extracts significantly (P < 0.05) decreased intestinal glucose absorption and promoted glucose uptake by the muscle. Moreover, following treatment of oxidatively damaged adipose with Ulva rigida and Ulva fasciata extracts, there was decreased levels of lipid peroxidation and increased glutathione peroxidase, superoxide dismutase, and catalase activities. The aqueous and ethanol extracts of Ulva rigida and Ulva fasciata revealed the presence of flavonoids and phenols when screened under Liquid Chromatogram Mass spectrometry (LCMS). Both Ulvan species demonstrated anti-hyperglycaemic and anti-hyperlipidaemic effects in a dose dependant manner. Further in vivo experimental studies are required to substantiate the present results. Additionally, future research on isolated compounds from the seaweed extracts that could be responsible for these observed effects are required towards the development of anti-diabetic and anti-obesity drugs.